The Effectiveness of Subintimal Balloon Angioplasty in the Treatment of Critical Lower Limb Ischemia in Patients with Diabetes Mellitus (Texas Journal of Medical Science, 2023)
The aim of the study is to present the immediate and long-term results of treatment of patients with diabetic foot syndrome using subintimal balloon angioplasty.